FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PADA PENERAPAN KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PEKERJA LAPANGAN DI PT PELINDO SUB REGIONAL BALI NUSRA - Wahyuni, Tri; Ani, Luh Seri (ARCHIVE OF COMMUNITY HEALTH; Vol 12 No 1 (2025): April 2025DO - 10.24843/ACH.2025.v12.i01.p03, 2025)
ABSTRACT The behavior of applying K3 is the habit of employees following the K3 standards or guidelines that apply in the company where they work. K3 behavior that is not good and not according to standardshas an impact on the incidence of work accidents, work-related diseases, and work-related diseases which are influenced by several factors. This study aims to determine the proportion of good behavior and factors related to the application of OSH to workers at PT Pelindo Sub Regional Bali Nusra. This research is a quantitative analytic observational study with a cross-sectional study design. The sampling technique used a total sampling technique with a total of 96 respondents. The results of the study show that as many as 46.82% of workers have good behavior in implementing OSH. The variable that has a relationship with K3 behavior is the use of personal protective equipment (p-0.03). Efforts to improve K3 behavior include providing training on how to use personal protective equipment properly and correctly and the company provides the tools needed by workers. Keywords : Use of Personal Protective Equipment, Occupational Health and Safety (K3) Implementation  Behavior